ANALISIS SIKLUS PENDAPATAN PADA CV. BORNEO BANGUN NUSA PALEMBANG - Rizal Effendi; Noviarni Noviarni (Universitas Tridinanti, 2021)
The goal of a company in general is to get as much profit as possible. One way to get a profit is by selling effectively and efficiently because sales are the main source of company revenue. The accounting information system for sales and cash receipts is one of the accounting information subsystems that explain how the procedures should be in carrying out sales activities and cash receipts from sales, so that manipulation of sales and cash receipts can be avoided. Procedures are a series of administrative activities that usually involve several or more people and are structured to ensure uniform treatment of company transactions that occur. In this sales and cash receipt accounting information system, it will inform users about how these activities are carried out, what documents are required, and which parties are authorized to authorize cash sales and receipts activities.Keywords: Procedures, sales, cash receipts